Corrosion Performance Of Nitrided Based Coating On AZ91 Mg Alloy In Hank’s Solution - Zainal Abidin, Muhammad Zaimi; Zulkifli, Mohd Rosli; Mohamad Juoi, Jariah; Mahamud, Zainab (Trans Tech Publications Ltd., 2015)
The use of Magnesium alloys as bioresorsable metallic implant is interesting to study due to the properties of magnesium ions which can be found naturally in bone tissue as well as are essential to human metabolism. However,its fast degradation rate and excess of these ions in the body may cause undesirable health effects. Therefore,surface treatment such as coating can offer an alternative solution to slow down the fast degradation rate of magnesium alloy.Thus,in this study,attempt has been made to coat the AZ91 magnesium alloy substrate with TiN,AlN and TiAlBN coatings using single hot press target with r.f. magnetron sputtering technique.During deposition,target power,working pressure and bias voltage were optimized for each coating deposition.Coating microstructure and its crystal phases are analysed using SEM and glancing angle X-ray diffraction analysis (GAXRD).Corrosion properties were evaluated using potentiodynamic polarization using Hank’s Solution as a medium to simulate body fluid.Result showed that TiAlBN coating is acting most successfully as a protection layer by slowing down the penetration of corrosion towards AZ91 Mg alloy substrate.SEM micrographs show a minimum damage to the substrate’s surface seen after subjected to corrosion test.In conclusion,TiAlBN coating is able to protect AZ91 Mg alloy substrate surface from corrosion and able to slow down their degradation rate.The better performance of TiAlBN coating create interest to further works on exploring the potential of this hard coated on AZ91 Mg alloy for biomaterial application.